The Rock-hewn Churches of Tǝgray (Ethiopia): New Studies in Qwälla and Dǝggwǝʽa Tämben and Säḥarti Samre districts. A Trip Report - Sergey Klyuev (Disegnare con, 2020)
The article is devoted to the results of a study of some little-known monuments of rock-hewn church architecture of the Tǝgray region (Ethiopia). The considered monuments are concentrated in the insufficiently explored by the scientists areas of Tǝgray: Qwälla and Dǝggwǝʽa Tämben, Säḥarti Samre. The paper represents new material obtained during the author's field studies of monuments, including descriptions, photographs and sketch-plans. The Author analyzes the features of rock-hewn churches of these areas, offers his version of the typological affiliation and dating of the monuments. In addition, attention is paid to the current state of preservation of monuments, the causes of their destruction and the dangers to their preservation in the future. DOI: https://doi.org/10.20365/disegnarecon.25.2020.4